1990
DOI: 10.1093/nar/18.16.4809
|View full text |Cite
|
Sign up to set email alerts
|

The cleavage specificity of RNase III

Abstract: We determined sites in X cil mRNA that are cleaved by RNase Ill in the presence of X OOP antisense RNA, using a series of OOP RNAs with different internal deletions. In OOP RNA-cil mRNA structures containing a potential region of continuous double-stranded RNA bounded by a non-complementary unpaired region, RNase Ill cleaved the cil mRNA at one or more preferred sites located 10 to 14 bases from the 3'-end of the region of continuous complementarity. Cleavage patterns were almost identical when the presumptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 33 publications
4
49
1
Order By: Relevance
“…The extra stem-loop structures of R. capsulatus and R. sphaeroides have strong similarity to secondary structures that are recognized by RNase III in E. coli, i.e., stems of less than 20 consecutive bp that contain unpaired bases forming internal loops (7). A sequence that fits the consensus sequence proposed for RNase III cleavage in E. coli by Krinke and Wulff (27) is not present within these Rhodobacter stem-loops. However, even in E. coli, functional RNase III sites can differ significantly from this consensus sequence (7).…”
Section: Resultsmentioning
confidence: 84%
“…The extra stem-loop structures of R. capsulatus and R. sphaeroides have strong similarity to secondary structures that are recognized by RNase III in E. coli, i.e., stems of less than 20 consecutive bp that contain unpaired bases forming internal loops (7). A sequence that fits the consensus sequence proposed for RNase III cleavage in E. coli by Krinke and Wulff (27) is not present within these Rhodobacter stem-loops. However, even in E. coli, functional RNase III sites can differ significantly from this consensus sequence (7).…”
Section: Resultsmentioning
confidence: 84%
“…Some of these transcripts show different patterns of expression, and the authors of that study suggested the presence of promoters internal to the operon. In the A. variabilis coxBAC operon, however, a sequence, 5Ј-AGAGATGACCA A-3Ј, strongly similar to RNase III cleavage sites (17) and located in a strand of the stem of a putative mRNA stem-loop structure, is detected in the region between the coxB and coxA open reading frames. The length from the coxB tsp to the possible cutting site is approximately 1,250 to 1,285 nucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…In two cases involving RNase III cleavage sites (41,49), GU pairs gave a strong mutant phenotype and so were thought to be disruptive of a structure which was stabilized by a GC pair at the same position. Since the sequence specificity of RNase III is relaxed (8,32), it is argued that these effects are due only to weakened pairing.…”
Section: Discussionmentioning
confidence: 99%